2012
DOI: 10.14723/tmrsj.37.223
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Nanopore Evolution in Track-Etched Poly(vinylidene fluoride) Membranes

Abstract: We investigated the formation of track-etched membranes of poly(vinylidene fluoride) (PVDF), a type of fluoropolymer, in detail, using conductometry. A 25 µm-thick PVDF film was irradiated with a 450 MeV 129 Xe or 2.2 GeV 197 Au ion beam, and then the latent tracks were etched in a 9 mol dm -3 aqueous potassium hydroxide solution at 80ºC in a conductometric cell. This paper focuses on the theoretical basis of the conductometric method and the apparatus used in our study. Representative results are then given i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, it has been reported that the fabrication of pores in glass with sub-micrometer diameter uses a femtosecond-pulsed laser [ 126 , 130 ] to measure paramecium bursaria chlorella virus 1 with a diameter of 175–190 nm [ 131 , 132 ]. Other reports have also shown the use of a single heavy ion to fabricate pores [ 125 , 133 , 134 ], while in another method, a needle is used to penetrate a membrane [ 135 ]. This method is used for pore preparation, sold as a pore membrane for qNano and Exoid by Izon Science, and is a necessary process for tunable resistive pulse sensing (TRPS) (The details of TRPS are discussed below).…”
Section: Pore-based Sensing For Virus Particles Detectionmentioning
confidence: 99%
“…For example, it has been reported that the fabrication of pores in glass with sub-micrometer diameter uses a femtosecond-pulsed laser [ 126 , 130 ] to measure paramecium bursaria chlorella virus 1 with a diameter of 175–190 nm [ 131 , 132 ]. Other reports have also shown the use of a single heavy ion to fabricate pores [ 125 , 133 , 134 ], while in another method, a needle is used to penetrate a membrane [ 135 ]. This method is used for pore preparation, sold as a pore membrane for qNano and Exoid by Izon Science, and is a necessary process for tunable resistive pulse sensing (TRPS) (The details of TRPS are discussed below).…”
Section: Pore-based Sensing For Virus Particles Detectionmentioning
confidence: 99%